2013
DOI: 10.1002/ps.3474
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the β2‐tubulin gene of Fusariumgraminearum and the β‐tubulin gene of Botrytiscinerea by homologous replacement

Abstract: The B. cinerea β-tubulin (Bctub) could complement the function of the two F. graminearum β-tubulins even when both were deleted. Expression of the β-tubulin conferring carbendazim resistance differs between pathogenic fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…5A). These results showed that FgTUB1 and FgTUB2 differ significantly in their functions during sexual reproduction, which was not reported in the previous study15. Overall, it appears that FgTUB1 plays an essential role in sexual development but FgTUB2 is more important for vegetative growth, confirming that functional divergence occurred between these two β-tubulin genes in F. graminearum .…”
Section: Resultscontrasting
confidence: 41%
See 3 more Smart Citations
“…5A). These results showed that FgTUB1 and FgTUB2 differ significantly in their functions during sexual reproduction, which was not reported in the previous study15. Overall, it appears that FgTUB1 plays an essential role in sexual development but FgTUB2 is more important for vegetative growth, confirming that functional divergence occurred between these two β-tubulin genes in F. graminearum .…”
Section: Resultscontrasting
confidence: 41%
“…Previous studies showed that, of the two β-tubulin genes, mutations in FgTUB2 but not in FgTUB1 have been shown to confer resistance to benomyl or MBC fungicides12. Furthermore, the two β-tubulin genes differ in their functions in hyphal growth15. To investigate the functional divergence of these two β-tubulin genes in F. graminearum , we then identified their orthologs in other sequenced Fusarium species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. cinerea has many ways of attacking hosts with mycelia, conidia or sclerotia can infect not only the leaves, stems and flowers, but also the fruits of plants, resulting in a huge decrease in yield, especially in commercial greenhouse tomato (Liu, Che, & Chen, ; Williamson et al, ). In agricultural production, the chemical control of grey mould is the primary method and it uses fungicides such as the benzimidazole fungicide (carbendazim), dicarboximide fungicide (procymidone), anilinopyrimidine fungicide (pyrimethanil) and succinate dehydrogenase inhibitor (SDHI) fungicide (boscalid) (Banno et al, ; Cong, He, Ma, Li, & Zhu, ; Duan et al, ; Fernandez‐Ortuno et al, ; Leroux, Chapeland, Desbrosses, & Gredt, ; Liu et al, ; Liu, Duan, Ge, Chen, & Zhou, ; Rosslenbroich & Stuebler, ; Zhang et al, ). In recent years, due to the long‐term use of these selective fungicides for the control of genetically variable B. cinerea , fungicides resistance and multiple resistance of B. cinerea have become rampant, resulting in a decline or failure in field control efficacy (Adnan, Hamada, Li, & Luo, ; Cosseboom, Ivors, Schnabel, Bryson, & Holmes, ; Fan, Hamada, Li, Li, & Luo, ; Fernandez‐Ortuno et al, ; Liu et al, , ; Ma & Michailides, ; Ma, Yan, Luo, & Michailides, ; Malandrakis, Markoglou, & Ziogas, ; Moyano, Gómez, & Melgarejo, ; Oshima et al, ; Qiu et al, , ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%